(untitled) (Research, Society and Development, 2022)
Introduction: Executive functions (EFs) involve three interconnected dimensions: working memory, cognitive flexibility and inhibitory control. Curcumin, present in Curcuma longa rhizomes or turmeric, has been used for its anti-inflammatory, antioxidant, anticancer, and neuroprotective effects, with potential for prevention/treatment of highly prevalent pathologies that burden healthcare systems, such as dementias. Methodology: This paper evaluated whether turmeric consumption by college students impacts their executive performance. University students underwent tests assessing FEs before and after nutritional supplementation with 1g/day of turmeric for 4 weeks. Results: Acute or chronic turmeric consumption had no significant impacts on tests assessing selective attention, working memory, abstract reasoning, cognitive strategy modification and problem solving. Conclusions: The absence of significant effects may be due to the characteristics of the experimental design that analyzed a young population with cognitive integrity. The low absorption/bioavailability of curcumin may also have influenced the results.